Caracterization of Liquid Smoke Bamboo Waste with Pyrolysis Method - Triastuti, Warlinda E.; Budhi, Primagita A.; Agustiani, Elly; Hidayat, Rizky A.; Retnoningsih, Rinny; Nisa’, Astri A. (Institut Teknologi Sepuluh Nopember, 2019)
This research was aimed to produce and to analyze the quality and chemical composition of liquid smoke from bamboo waste by pyrolisis process. Temperatur of pyrolisis reactor were 140 oC, 180 oC, 220 oC, 260 oC and 300 oC for 5 hours to produce liquid smoke. Liquid smoke purified by filtration, distillation and adsorption. Resulted liquid smoke were analyzed yield, acidity, and density. Identifying the chemical composition of liquid smoke was by Gas Chromatography and Mass Spectrometry (GC-MS). Yield of liquid smoke 1,6977% up to 3,9713 %; Acidity of liquid smoke were 1.49 up to 1,9; the density of liquid smoke 1,004 up to 1,045. The results of GC-MS test showed that chemical composition of the liquid smoke have Phenolic compounds 0,5 – 0,6ppm and liquid smoke found not containing of carsinogenic Benz (a) Pyrene.